2002
DOI: 10.1093/jat/26.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Determination of MDMA and its Metabolites in Blood and Urine by Gas Chromatography-Mass Spectrometry and Analysis of Enantiomers by Capillary Electrophoresis

Abstract: A gas chromatography-mass spectrometry (GC-MS) method was used for the simultaneous quantitation of 3,4-methylenedioxymethamphetamine (MDMA) and the 3,4-methylenedioxyamphetamine (MDA), 4-hydroxy-3-methoxymethamphetamine (HMMA), and 4-hydroxy-3-methoxyamphetamine (HMA) metabolites in plasma and urine samples after the administration of 100 mg MDMA to healthy volunteers. Samples were hydrolyzed prior to a solid-phase extraction with Bond Elut Certify columns. Analytes were eluted with ethyl acetate (2% ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 27 publications
3
75
1
4
Order By: Relevance
“…MDMA and MDA were dissolved in methanol for stock and working solutions for analysis. HHMA and HHA were synthesized as described previously (Ensslin et al, 1996;Pizarro et al, 2002) and prepared in methanol for stock dmd.aspetjournals.org and working solutions. Sodium metabisulfite (Sigma, St. Louis, MO) was dissolved in sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…MDMA and MDA were dissolved in methanol for stock and working solutions for analysis. HHMA and HHA were synthesized as described previously (Ensslin et al, 1996;Pizarro et al, 2002) and prepared in methanol for stock dmd.aspetjournals.org and working solutions. Sodium metabisulfite (Sigma, St. Louis, MO) was dissolved in sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…Mephedrone-D3 was used as internal standard. MDMA concentrations in plasma were measured by GC/MS (Pizarro et al, 2002). Human pharmacology of mephedrone E Papaseit et al…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…We showed that the catechol-metabolites that significantly reduced THLE cell viability were also responsible for the reduction of GSH, which was in line with results from other studies (Carvalho et al 2002; To verify these findings in a model where metabolism can occur, we used primary rat hepatocytes. However, catechol-metabolites are the main metabolites formed in humans (Segura et al 2001;Pizarro et al 2002;, while in rats the main MDMA-metabolite is the non-cytotoxic MDA (Cho et al 1990;Lin et al 1992). Indeed, the levels of GSH and cell viability were not significantly decreased in primary rat hepatocytes upon MDMA exposure.…”
Section: Phase II Metabolismmentioning
confidence: 99%